Respiratory muscle strength in Hashimoto's disease - Seda Beyhan Sagmen; Naile Gokkaya (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2020)
Objective: The present study aimed to investigate the respiratory function and respiratory muscle strength in Hashimoto's disease. Material and methods: Thirty-two patients newly diagnosed with Hashimoto’s disease between January 2017 and July 2017 were included in this study. Pulmonary function tests were also performed. FEV1 / FVC, FEV1%, FEV1 (1/sec), FVC (%), FVC (1), DLCO, DLCO/VA, maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP) values were examined. Results: The mean age of the hypothyroid group was 43 (36-45), and the euthyroid group was 40 (35-46) years. The DLCO/VA level [86.00 (79.00-99.00)] in the hypothyroid group was significantly lower than the euthyroid group [99.00 (95.00-115.00)] (p: 0.007). MIP level in the hypothyroid group [75.00 (69.00-79.00)] was significantly lower than the euthyroid group [99.00 (83.00-112.00)] (p: 0.008). A negative correlation was found between TSH and DLCO, DLCO/VA and MIP (r: -0.376, p: 0.034; r: -0.499, p: 0.004 and r: -0.378, p: 0.033). A positive correlation was found between T4 and DLCO and DLCO/VA (r: 0.390, p: 0.027 and r: 0.351, p: 0.049, respectively). Conclusion: In light of the data obtained in this study, the findings suggest that hypothyroidism affects respiratory muscle strength, and this weakness is associated with thyroid hormone levels